Integrated Network Pharmacology and Experimental Validation Approach to Investigate the Therapeutic Effects of Capsaicin on Lipopolysaccharide-Induced Acute Lung Injury - Liu, Peihui; Hao, Jindou; Zhao, Jie; Zou, Rong; Han, Juan; Tian, Jia; Liu, Wanqu; Wang, Hao (Mediators of Inflammation, 2022)
An integrated method combining network pharmacology and in vivo experiment was performed to investigate the therapeutic mechanism of capsaicin (Cap) against acute lung injury. The potential key genes and signaling pathways involved in the therapeutic effect of Cap were predicted by the network pharmacology analyses. Additionally, the histological assessment, ELISA, and RT-qPCR were performed to confirm the therapeutic effect and the potential mechanism action involved. Our findings showed that TNF, IL-6, CXCL1, CXCL2, and CXCL10 were part of the top 50 genes. Enrichment analysis revealed that those potential genes were enriched in the TNF signaling pathway and IL-17 signaling pathway. In vivo experiment results showed that Cap alleviated histopathological changes, decreased inflammatory infiltrated cells and inflammatory cytokines, and improved antioxidative enzyme activities in the bronchoalveolar lavage fluid (BALF). Furthermore, Cap treatment effectively downregulated TNF, IL-6, NF-κB, CXCL1, CXCL2, and CXCL10 in lung tissue. Thus, our findings demonstrated that Cap has the therapeutic effect on LPS-induced acute lung injury in neonatal rats via suppression of the TNF signaling pathway and IL-17 signaling pathway.